Kasultanan Samawa di Pulau Sumbawa dalam Kurun Waktu Abad XVII – XX - Tawalinuddin Haris (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
Kasultanan Samawa is one of Islamic Kingdoms in Sumbawa Island. This Kingdom involves Sumbawa Besar and West Sumbawa regencies. Samawa Kingdom was established in the mid of17th Century up to 1958. This Kongdom has been led by 18 or 19 kings or sultans. The first sultan was Mas Pamajaan,and the last Sultan was Muhammad Kaharuddin. This article a Sumawalive work of the research on Kesultanan Samawa in the XVII-XX century, which was conducted in 2015.